2022
DOI: 10.1038/s41594-022-00757-z
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated conformational changes in the V1 complex during V-ATPase reversible dissociation

Abstract: Vacuolar-type ATPases (V-ATPases) are rotary enzymes that acidify intracellular compartments in eukaryotic cells. These multi-subunit complexes consist of a cytoplasmic V1 region that hydrolyzes ATP and a membrane-embedded VO region that transports protons. V-ATPase activity is regulated by reversible dissociation of the two regions, with the isolated V1 and VO complexes becoming autoinhibited upon disassembly and subunit C subsequently detaching from V1. In yeast, assembly of the V1 and VO regions is mediated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 66 publications
(95 reference statements)
3
40
0
Order By: Relevance
“…However, 3D variability analysis of particle images (Punjani and Fleet, 2021) from both rotary states revealed that the C-terminal domain of subunit H could adopt two different conformations, with the consensus map missing the domain due to incoherent averaging. In one extreme of the principal component analysis, subunit H adopts the conformation seen in previous structures of intact V-ATPase (Benlekbir et al, 2012; Tan et al, 2021; Vasanthakumar et al, 2019, 2022; Wang et al, 2020a, 2020b; Zhao et al, 2015), with the C-terminal domain of H bound to the N-terminal domain of subunit a (Fig. 3B and C).…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…However, 3D variability analysis of particle images (Punjani and Fleet, 2021) from both rotary states revealed that the C-terminal domain of subunit H could adopt two different conformations, with the consensus map missing the domain due to incoherent averaging. In one extreme of the principal component analysis, subunit H adopts the conformation seen in previous structures of intact V-ATPase (Benlekbir et al, 2012; Tan et al, 2021; Vasanthakumar et al, 2019, 2022; Wang et al, 2020a, 2020b; Zhao et al, 2015), with the C-terminal domain of H bound to the N-terminal domain of subunit a (Fig. 3B and C).…”
Section: Resultsmentioning
confidence: 65%
“…Previous structural studies of yeast V-ATPase have relied on purification of the detergent-solubilized endogenous enzyme following incorporation of sequence encoding an affinity tag into the yeast chromosomal DNA (Benlekbir et al, 2012; Mazhab-Jafari et al, 2016; Oot et al, 2016; Roh et al, 2018; Vasanthakumar et al, 2022; Zhao et al, 2015). V-ATPase from bovine brain, where the enzyme is highly enriched, was isolated for structural studies using a large mass of starting material and conventional chromatographic methods (Wang et al, 2020b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations